PHARMACEUTICAL AND MICROBIOLOGICAL STANDARDIZATION OF SICULINE SYRUP® FORMULATION, AN ANTISICKLING HERBAL MEDICINE - OYEDELE, AYOBAMI OLUTAYO; Elujoba, Anthony Adebolu; Olayemi, Uduak Ime (African Journal of Traditional, Complementary and Alternative Medicines, 2020)
Background: This study utilized 4:1 combination ratio of Carica papaya fruit mesocarp and Sorghum bicolor leaf fermented extract freeze-dried and named Siculine extractive (SE) as the active principle to develop Siculine syrup as an herbal formulation with potent antisickling properties. Materials and Methods: In-vitro antisickling (inhibitory or reversal) activities of test (SE) and control samples were determined on sodium metabisulphite-induced sickled red blood cells collected from confirmed non-crisis sickle cell patients. Particulate, pH and microbiological qualities of SE were determined toward its use in formulation. The activities of SE aqueous dispersion (1-6 mg/ml) and of the formulated Siculine syrup® were evaluated using buffered normal saline (negative control), vanillic acid, parahydroxy benzoic acid (PHBA) and Ciklavit® (an herbal antisickling commercial product), as positive controls. Results: The processed plant materials yielded 17.7±1.4 %w/w of water-insoluble, amber coloured particles (27.4 – 274.0 μm size range) of SE powder with microbiological quality suitable for oral liquid formulation. SE aqueous dispersion, neutral in pH, demonstrated concentration-related sickling inhibitory and reversal activities. The 5.0 mg/ml aqueous dispersion exhibited optimum antisickling potential namely, 80 % inhibitory and 66 % reversal effects, which were statistically equivalent to activities of the Siculine syrup® formulation, reference Ciklavit®, and 4.0-6.0 mg/ml PHBA’s reversal activity, but higher than the inhibitory activity of 4.0-6.0 mg/ml vanillic acid. Conclusion: Siculine syrup® formulation containing 10, 2, 0.5, and 0.25 %w/v of sucrose, tragacanth, SE, and parabens, respectively, demonstrated optimal physicochemical and microbiological stability properties with strong antisickling activities comparable to those of Ciklavit®.